Examining the Importance of Pretreatment to Capture and Analyze Microfibers from Textile Wastewater - AKYILDIZ, SİNEM HAZAL; YALÇIN, BAHATTİN (My University, 2022)
The textile industry is one of the causes of environmental problems, which have a negative effect on all organisms in the ecosystem. In addition to the textile wastes generated by the textile industry, wet processes (dyeing, rinsing, softening, mechanical/chemical finishing) release inorganic compounds, polymers, organic products, dyes, and microfibers (MFs) into the environment. Microfibers may also accumulate in marine species and be passed to higher trophic levels, including humans, through the food chain. In order to solve this problem, it is first necessary to correctly identify it. These stages are sample pretreatment, microplastic separation, and characterization/quantification. The aim of this research is to assess the significance of sample pretreatment in detecting microfibers in wastewater from various parts of a textile company. For the purpose of observing the effect of organic removal, half of the wastewater from each process was pretreated, while the other half was not. A 6-hour pretreatment at 60 °C with Fenton's reagent was performed. A microscope and FTIR were used to investigate the MFs collected on the filter. In particular, due to the rich amount of organic matter in inflow and outflow wastewater, the lack of pretreatment made the analysis very difficult. Additionally, the FTIR analysis failed to detect some of the distinctive peaks that should have been visible in the materials.
Keywords: Tekstil Mühendisliği ve Teknolojisi; Mühendislik ve Teknoloji; Textile Engineering and Technology; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Malzeme Bilimi; MALZEME BİLİMİ, TEKSTİL; Engineering, Computing & Technology (ENG); MATERIALS SCIENCE; MATERIALS SCIENCE, TEXTILES; – Microplastic pollution; microfiber; wastewater pretreatment; organic removal; Fenton’s reagent